Thrombophilic mutations in pre-eclampsia and pregnancy-induced hypertension - Omar, S.Z.; Qvist, R.; Khaing, S.L.; Muniandy, S.; Bhalla, S. (2008)
Aim: The aim of the present study was to determine the existence or prevalence of thrombophilic markers such as Factor V Leiden, prothrombin G20210A, protein S, protein C, activated protein C and anti-thrombin in pre-eclampsia and pregnancy-induced hypertensive patients. Methods: Blood samples were collected from a total number of 124 women at the maternity unit, University of Malaya Medical Center. These included 49 patients with pre-eclampsia, 63 patients with pregnancy-induced hypertension and 12 normal pregnant women. DNA was extracted from the blood samples. Factor V Leiden (Taq I) and prothrombin G20210A (Hind III) genotyping was done on polymerase chain reaction-restriction fragment length polymorphism. Anti-thrombin activity and the concentrations of protein C, protein S and activated protein C were measured using the IL Coagulation System (Hemosil). Results: Of the 124 subjects, one pre-eclampsia patient was homozygous for Factor V Leiden mutation but prothrombin G20210A mutation was not present in any of the subjects. The subject with Factor V Leiden mutation also had a low activated protein C resistance and a low protein S concentration. Conclusions: Factor V Leiden mutation is present in the Asian population and may very well serve as one of the genetic factors responsible for pre-eclampsia and other adverse pregnancy outcomes.